Pengaruh Kebijakan Dividen, Book Value Per Share (Bvps), Leverage Terhadap Volatilitas Harga Saham Pada Perusahaan Rokok Yang Listing Di Bursa Efek Indonesia Tahun 2016-2018 - Salma Silvia Nazihah; Nur Hidayati; M. Ridwan Basalama (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis research is conducted on Indonesia Stock Exchange which aims to determine the influence of dividend policy, book value per share (BVPS), leverage on stock price volatility. The research time used for 3 years is 2016-2018.Research populations on cigarette companies wich listing On Indonesia Stock Exchange period 2016-2018. Samples taken using the purposive sampling method. The number of samples there are 3 companies and the data used is secondary data. The method used is double linear regression with a level of significant of 0.05.The results of this study: (1) Dividend policy affects positively and significantly against stock price volatility. It is present with T count value of – 1,505 And significance value of 0.035 (smaller than 0.05). (2) Book Value Per Share (BVPS) Insignificant effect on the stock price volatility. It is indicated by the calculated T value of-0.548 and the significance value of 0.147 (greater than 0.05). (3) Leverage has no significant effect on stock price volatility. It is indicated by the calculated T value of-0.935 And significance value of 0.188 (greater than 0.05). Test result F count has a value of 6.049 with a significance of 0.041 and an adjusted value of R-square of 0.654. It can be explained that the ability of independent variables in dependent variables is 65.4% of the remaining 34.6% described by other independent variables outside of this research model. Keywords: Dividend, Book Value Per Share (BVPS), Leverage, stock price volatility.